22ND Opened seminar on acoustics - Zbigniew ŻYSZKOWSKI (Archives of Acoustics)
The Seminar was held September 8-13, 1975 at Świerardów Zdrój. The promotor of the Seminar was the Wrocław Section of Polish Acoustics Society as well as the Institute of Telecommunication and Acoustics of Wrocław Technical University.